2016
DOI: 10.4240/wjgs.v8.i7.492
|View full text |Cite
|
Sign up to set email alerts
|

Early surgery in Crohn’s disease a benefit in selected cases

Abstract: Our data supports other recent studies suggesting that patients with ileocolonic CD may have a more benign disease course if undergoing early surgical intervention, with fewer admissions to hospital and a trend to reduced overall operation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…Successive resections leading to progressive shortening of the small bowel can have devastating clinical consequences. However, recent studies have demonstrated the benefit of early resection, indicating that optimal treatment of CD (especially ileocecal disease) does not necessarily dictate minimizing resection [42, 43]. Thus, understanding whether biologics can affect recurrence and re-operation rates following an initial operation is an important factor in operative planning.…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…Successive resections leading to progressive shortening of the small bowel can have devastating clinical consequences. However, recent studies have demonstrated the benefit of early resection, indicating that optimal treatment of CD (especially ileocecal disease) does not necessarily dictate minimizing resection [42, 43]. Thus, understanding whether biologics can affect recurrence and re-operation rates following an initial operation is an important factor in operative planning.…”
Section: Crohn’s Diseasementioning
confidence: 99%
“…These complications were identified in the studied group of patients in varying percentages -but there was a tendency towards surgical interventions in emergency settings in contradiction with literature where there is a changing trend towards surgery in elective settings (1). The benefit of early surgery in selected ileocolic CD cases seems to offer future better results regarding surgical reinterven-tions and hospital admissions when compared to medical therapy as demonstrated by the study group of Vinna An et al on 157 patients (5). This evolution of elective surgery is also sustained by Christopher Ma et.…”
Section: Discussionmentioning
confidence: 64%
“…It has been reported that 20%-40% of patients with CD require surgery in the first year after diagnosis, and up to 80% require surgery at some time during their disease. 10 When patients with CD have acute complications such as intestinal obstruction, fistula, perforation or stenosis, or when medical treatment is ineffective or intolerable, surgery is usually inevitable. And long-term studies have shown that after resection, 50% of patients will never require reoperation.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence suggests that early surgery in patients with CD may lead to a longer time to clinical recurrence and a lower long-term reoperation rate (14% at 5 years) compared with later surgery (30% at 5 years). 10 The 'Laparoscopic ileocaecal resection versus infliximab for terminal ileitis in Crohn's disease' (LIR!C) trial compared laparoscopic ileocaecal resection with IFX therapy for patients with Crohn's terminal ileitis who failed conventional therapy, and through the study, researchers found that the early surgery and IFX groups had similar endoscopic remission at 1 year, while the surgery group had better general quality of life and less medical consumption. 20 Therefore, compared with the initial IFX treatment, we hold the opinion that early surgery can further reduce the side effects of drugs, improve the quality of life and reduce medical expenses.…”
Section: Introductionmentioning
confidence: 99%